PPTSD Portrait due to Childhood Trauma to Ellice in the All Her Little Secrets Novel - Azizah, Azizah; Praptawati, Destary (Universitas PGRI Semarang, 2024)
Almost everyone has experienced traumatic events that lead to trauma. Trauma is a form of psychological experience that has a serious impact on mental health. The impact of trauma itself can vary, such as anxiety, depression, dissociation, and PTSD. In the novel All Her Little Secrets, Ellice, the main character, is described as suffering from PTSD due to childhood trauma. This study aims to determine how the character Ellice is described as suffering from PTSD and what trauma she has experienced. This research uses a qualitative descriptive method referring to two types of data, namely primary data and secondary data. Primary data were taken from the All Her Little Secrets novel in the form of narrative, dialogue and monologue. Meanwhile secondary data were taken from journals, books and articles related to the research topic. Several steps were taken to obtain data, namely reading the novel repeatedly and carefully, identifying data, classifying data, and reducing power. The results of this study concluded that Ellice as a PTSD sufferer was described through the symptoms she experienced. Ellice's PTSD symptoms include re-experiencing, avoidance, negative alterations in cognition and mood, and hyperarousal. Meanwhile, the forms of childhood trauma that Ellice experienced included bullying, child maltreatment, and exposure to domestic and community violence